Comprehensive three‐dimensional morphology of neoangiogenesis in pulmonary veno‐occlusive disease and pulmonary capillary hemangiomatosis. (27th February 2019) - Neubert, Lavinia; Borchert, Paul; Shin, Hoen‐Oh; Linz, Friedemann; Wagner, Willi L; Warnecke, Gregor; Laenger, Florian; Haverich, Axel; Stark, Helge; Hoeper, Marius M; Kuehnel, Mark; Ackermann, Maximilian; et al.
Abstract: Pulmonary veno‐occlusive disease (PVOD) is a rare lung disease characterized by fibrotic narrowing of pulmonary veins leading to pulmonary hypertension (PH) and finally to death by right heart failure. PVOD is often accompanied by pulmonary capillary hemangiomatosis (PCH), a marked abnormal proliferation of pulmonary capillaries. Both morphological patterns often occur together and are thought to be distinct manifestations of the same disease process and accordingly are classified together in group 1′ of the Nice classification of PH. The underlying mechanisms of these aberrant remodeling processes remain poorly understood. In this study, we investigated the three‐dimensional structure of these vascular lesions in the lung explant of a patient diagnosed with PVOD by μ‐computed tomography, microvascular corrosion casting, electron microscopy, immunohistochemistry, correlative light microscopy and gene expression analysis. We were able to describe multifocal intussusceptive neoangiogenesis and vascular sprouting as the three‐dimensional correlate of progressive PCH, a process dividing pre‐existing vessels by intravascular pillar formation previously only known from embryogenesis and tumor neoangiogenesis. Our findings suggest that venous occlusions in PVOD increase shear and stretching forces in the pulmonary capillary bloodstream and thereby induce intussusceptive neoangiogenesis. These findings can serve as a basis for novel approaches to the analysis of PVOD.